POLITIK POPULISME NURDIN ABDULLAH: DARI BANTAENG MENUJU SULSEL-01 - Ade Irma Surani Haliq; Reksa Burhan; sunardi (Program Studi Pemikiran Politik Islam, Fakultas Ushuluddin, Adab, dan Dakwah IAIN Palu, 2022)
The face of democracy in Indonesia is now starting to lead to the emergence of populism in democracy in Indonesia. A number of existing studies have concluded about the rise of populism as a phenomenon in electoral democracy. This article will look at the forms and patterns of populism played by actors at the local level in the arena of electoral democracy. By taking a case study, in South Sulawesi. The emergence of Nurdin Abdullah as a populist political actor won the electoral battle at the local level. By using a literature study, this article builds an argument. Although populism does not contradict democracy, populism also has its limitations. Populism strengthens when social and political institutions are functionally problematic, so the emergence of charismatic political actors is an unavoidable alternative.